Validation of human small airway measurements using endobronchial optical coherence tomography. Issue 11 (November 2015) - Chen, Yu; Ding, Ming; Guan, Wei-jie; Wang, Wei; Luo, Wei-zhan; Zhong, Chang-hao; Jiang, Mei; Jiang, Ju-hong; Gu, Ying-ying; Li, Shi-yue; Zhong, Nan-shan
Abstract: Background: Small airway remodeling is the cardinal feature underlying chronic airway diseases. There is no modality which identifies small airway pathological changes, which is crucial for early diagnosis, efficacy and prognostic assessment. Objective: To evaluate the usefulness of endobronchial optical coherence tomography (EB-OCT) in assessing small airways morphology in vivo . Methods: Twelve patients with pulmonary nodules scheduled for lung resection underwent spirometry, multi-detector computed tomography (MDCT) and EB-OCT. We measured Dmean (mean luminal diameter), Ai (inner luminal area), Aw (airway wall area) and Aw% [Aw/(Ai + Aw) × 100%] from the 3rd to 5th generation bronchi of RB9 segment by MDCT. Dmean, Ai, Aw and Aw% from the 3rd to 9th generation bronchi of RB9 segment were measured by EB-OCT and histology. Correlations of these parameters, measured by three different methods, were evaluated. We recruited 4 COPD patients to determine if EB-OCT could identify peripheral airway remodeling. Results: The 4 parameters, measured by CT and EB-OCT, correlated significantly [Dmean (r = 0.991), Ai (r = 0.997), Aw (r = 0.997), Aw% (r = 0.991), all P < 0.01]. Significant correlation were found for these parameters, measured by histology and EB-OCT, from the 3rd to 5th generation bronchi [Dmean (r = 0.989), Ai (r = 0.997), Aw (r = 0.999), Aw% (r = 0.988), all P < 0.01], and from the 6th to 9th generation bronchi [Dmean (r = 0.979), Ai (r = 0.997), Aw (r = 0.994) and Aw% (r = 0.988), all P < 0.01]. Significant small airways morphological abnormalities were observed in COPD patients. Conclusions: EB-OCT, a minimally invasive imaging modality with high-resolution, is useful and clinically practical for assessing proximal and distal airways of human compared with CT and histology. Graphical abstract: We have elected to submitFig. 1 for the Graphic abstract. The legend is as follows: EB-OCT probing guided by navigation system. Ultrafine bronchoscope with C7 Dragonfly OCT probe (C), guided by the navigation system. (A)Vision of ultrafine bronchoscope; B) Real-time synchronous operation with navigation from the trachea (generation 0) to the 9th generation bronchi (D); Initiation of scanning (E). Highlights: Small airway (up to 9th generation bronchi) architecture has been characterized using endobronchial OCT in humans in vivo . Distal airways could be precisely measured by OCT combined with ultrafine bronchoscope and navigational technique. Validated with CT and pathology findings, OCT reliably detected small airway remodeling at early-stage respiratory diseases. OCT offers a novel and promising approach for small airway architecture measurement at high resolution.